Reception Analysis Study on Marketing Communication Strategies in Wardah Cosmetic Advertisements ("Shampoo – the Real Hijab Expert") - Hebby Ilma Dini; Sri Hastjarjo; Ign. Agung Satyawan (Formosa Journal of Social Sciences (FJSS), 2023)
Shampoo – The Real Hijab Expert, this product is segmented for Muslim women who wear the hijab. This research was conducted to find out about the audience of wardah advertisements, especially for Muslim women in Islamic organizations who have various backgrounds regarding the contents of messages in wardah cosmetic advertisements "Shampoo - The Real Hijab Expert". This study uses a qualitative methodology, namely through the method by conducting an interview with several predetermined informants. And this research uses a theory in the form of Encoding-Decoding from Stuart Hall. The findings in this study indicate that there are several categories in analyzing reception from audiences based on a variety of different backgrounds. From the findings of this study, there are 2 (two) categories, namely Dominant Hegemonic, Negotiated Reading and there is no Oppositional in this study